Rajiv gandhi to Narendramodi; Broken Polity,flickering reforms - Parsa Venkateshwar Rao Jr (Sage, 2019)
For the first time, the political story of India from the mid-1980s to the second decade of the present century is reconstructed through the first-person narratives of political leaders, revealing their inmost thoughts in their public utterances, offering weak arguments for their unforgivable lapses, speaking in eloquent terms of their achievements and sometimes showing uncharacteristic humility in what they said in their public speeches, in the Lok Sabha, in their blogs.